2018
DOI: 10.1016/j.jep.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Equisetum giganteum L and Copaifera reticulate Ducke show strong antiviral activity against the sexually transmitted pathogen herpes simplex virus type 2

Abstract: These studies show that extracts of Equisetum giganteum L and Copaifera reticulate Ducke have potent antiviral activities against HSV-2 comparable to those two previously identified plants, Croton lechleri Müll. Arg. and Uncaria tomentosa (Willd. ex Schult.) DC. These studies confirm that plants used by the Tacana tribe could be explored further for the development of novel topical antiviral microbicides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
1
7
0
2
Order By: Relevance
“…As can be seen from the results presented in igure 3 the highest and most effective inhibition of all tested viruses infection was obtained when the treatment with the product was at the time and after infection (about 100% inhibition). These results are in agreement with previous studies reported that the anti-virally active natural products mainly prevent early steps of the viral infection such as direct effect on the viral particles, virus adsorption and/or penetration into the host cells [5,14,38,40,46]. When the cells were treated only at the time of infection or only p.i.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As can be seen from the results presented in igure 3 the highest and most effective inhibition of all tested viruses infection was obtained when the treatment with the product was at the time and after infection (about 100% inhibition). These results are in agreement with previous studies reported that the anti-virally active natural products mainly prevent early steps of the viral infection such as direct effect on the viral particles, virus adsorption and/or penetration into the host cells [5,14,38,40,46]. When the cells were treated only at the time of infection or only p.i.…”
Section: Resultssupporting
confidence: 93%
“…The latent virus is reactivated spontaneously causing recurrent infections in infected patients [6]. Although it can effectively be treated with nucleoside analogs such as acyclovir (ACV), but still the search for new effective antiherpetic drugs is important due to the development of ACV-resistant herpes viruses mutants particularly in immunosuppressed and in immunode iciency syndrome patients [7][8][9][10][11][12][13][14][15]. In addition, ACV and other available nucleoside analogs have different undesired side effects (like nausea, vomiting, headache and others) [16] and are not highly effective against reactivated herpes viruses [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, drug resistance rates are increasing, especially among immunosuppressed individuals (Dai et al, 2018). There is currently no effective HSV-2 vaccine (Churqui et al, 2018), so the exploration of natural plant pharmaceuticals and their active components has become . VK2/E6E7, HSV-2 solution, and drugs (or medium) were co-incubated at 37°C for 24 h. C stands for control group, V stands for model group, JZ sands for different concentrations of JZ-1 group, JV sands for JZ-1 treatment group, PV stands for penciclovir treatment group, BV stands for berberine treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral activity against HSV-2 (strain 333) of hydroethanolic extracts of Equisetum giganteum, Croton lechleri, Uncaria tomentosa, and Copaifera reticulata was investigated by Churqui et al 73 Viral plaques were reduced by 100% by extracts of E. giganteum, U. tomentosa, and C. reticulata at a concentration of 100 mg/ml and the C. lechleri extract at 30 mg/ml. IC 50 values for the E. giganteum, U. tomentosa, C. reticulata, and C. lechleri extracts were found to be 18 mg/ml, 28 mg/ml, 50 mg/ml, and 10 mg/ml, respectively, and SI values were calculated as >55.56, >35.71, 10, and >100, respectively.…”
Section: Multiple Geographic Locationsmentioning
confidence: 99%